Kebijakan Ekonomi Biru dan Keberlanjutan UMKM di Kawasan Pesisir - Kusnindar, Arum Arupi; Khoiriyah, Siti; Pasya, Dhel Juni; Dwi, Bilqis (Civiliza Publishing, 2025)
This study aims to analyze the implementation of the blue economy in supporting the sustainability of micro, small, and medium enterprises (MSMEs) in coastal areas. Referring to the Sustainable Development Goals (SDGs) indicators, this study explores the role of the blue economy in improving social welfare, economic growth, and environmental conservation. This study uses a qualitative method with data collection through in-depth interviews with MSME actors in coastal areas. The data is processed using Nvivo. The analysis shows that the implementation of the blue economy supports various aspects of the SDGs, such as poverty alleviation, job creation, environmental conservation, and improving food security. Business actors around coastal areas are well aware that the sustainability of their business depends on coastal natural conditions so that awareness to preserve the environment is very high. However, challenges related to capital, technology access, and policy support remain major obstacles. Recommendations include strengthening strategic partnerships, training in environmentally friendly technologies, and developing sustainable business models. The results of the study also show the need for closer collaboration between local governments and universities in providing coaching and mentoring. The results of this study provide important insights for policy making and development of blue economy-based MSMEs to support the sustainability of coastal areas.